Drug-induced torsades de pointes: Disproportionality analysis of the United States Food and Drug Administration adverse event reporting system - Wu, Ziyang; Zhou, Pengxiang; He, Na; Zhai, Suodi (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to identify the most common and top drugs associated with the risk of torsades de pointes (TdP) based on the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. Methods: We used OpenVigil 2.1 to query FAERS database and data from the first quarter of 2004 to the third quarter of 2021 were retrieved. The Medical Dictionary for Regulatory Activities (MedDRA) was used to identify TdP cases. We listed the most common drugs associated with the reported TdP cases. Then, the reporting odds ratio (ROR) and the proportional reporting ratio (PRR) for the reporting association between different drugs and TdP risk were calculated. Meanwhile, comparisons were conducted with the QT drug lists of CredibleMeds® in an attempt to identify drugs with a potential risk of TdP that were not on the list. Results: A total of 9,217,181 adverse event reports were identified, of which 3,807 (0.04%) were related to TdP. TdP were more likely to occur in the elderly and females. Amiodarone (464 cases) was associated with most cases of TdP. According to the disproportionality analysis, the top five drugs with the highest ROR and PRR were tolazoline (ROR 1615.11, 95% confidence interval [CI] 455.59 - 5725.75, PRR 969.46, χ2 2960.10), levomethadyl (ROR 1211.01, 95% CI 302.75 - 4844.04, PRR 807.67, χ2 1677.03), ibutilide (ROR 1118.74, 95% CI 425.00 - 2944.91, PRR 765.77, χ2 3845.27), halofantrine (ROR 660.55, 95% CI 184.21 - 2368.69, PRR 519.22, χ2 1076.31) and isoproterenol (ROR 352.20, 95% CI 227.19 - 546.00, PRR 307.82, χ2 6692.53). Approximately half of the top 50 drugs (22 for ROR, 30 for PRR) were not outlined on the QT drug lists of CredibleMeds®. Conclusion: Approximately half of the top risk drugs (22 for ROR, 30 for PRR) were not outlined in the QT drug lists of CredibleMeds®. Notably, potential risks are of great importance and should be closely monitored in clinical practice. Also, further research is needed to investigate the association between these drugs and TdP.